(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nanotechnology has developed a great deal of interest in several fields including agriculture, manufacturing, medicine sector and public health, due to the demands and applications of nano materials. Increasing use of nano materials has resulted in concerns about environmental impacts in every field of society. Environmental exposure to nano materials is unavoidable as nano materials become part of our everyday lives, and as a result, research into nano toxicity is gaining interest. This study provided an overview of recent research efforts on existence, actions and toxicity of various groups of environmental nano materials.